Determinan Kualitas Audit pada Sektor Basic Materials (2020-2024) - Siti Zainab; Novita Weningtyas Respati (Universitas Negeri Padang, 2026)
This study examines the determinants of audit quality in basic materials companies on the Indonesia Stock Exchange (2020–2024), amid increasing public skepticism toward the profession. Using a purposive sampling method, a sample of 52 firms was selected over a five-year period, yielding 260 firm year observations for panel data analysis. The research analyzes the impact of audit committees, audit fees, audit tenure, audit firm size, and time budget pressure. The findings reveal that only the committee has a significant positive effect on audit quality, whereas audit fees, audit tenure, audit firm size, and time budget pressure have no significant effect. Effective audit committee oversight, as emphasized in SA 260 and SA 265 (2025), emerges as a key driver of audit quality, suggesting that strengthening audit committee effectiveness is essential for improving audit quality in the basic materials sector. Professional integrity and compliance with SPAP and KEPAP also remain fundamental safeguards for maintaining audit quality. Future research should explore additional determinants, adopt more representative audit quality proxies, refine the measurement of time budget pressure, and examine broader industry settings to improve the generalizability of findings.